2013
DOI: 10.1371/journal.pone.0082294
|View full text |Cite
|
Sign up to set email alerts
|

Tryptanthrin Inhibits Angiogenesis by Targeting the VEGFR2-Mediated ERK1/2 Signalling Pathway

Abstract: Angiogenesis is a key step for tumour growth and metastasis, and anti-angiogenesis has been proposed as an important strategy for cancer therapy. Tryptanthrin is a weakly basic alkaloid isolated from the dried roots of medicinal indigo plants and has been shown to possess anti-tumour activities on various cancer cell types. This study aims to investigate the in vitro and in vivo anti-angiogenic activities of tryptanthrin and to unravel its underlying molecular action mechanisms. Our results show that tryptanth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 49 publications
0
44
0
Order By: Relevance
“…Chemistry Benzo [5,6]indolo[2,1-b]quinazoline-6,14-dione (benzo[b]tryptanthrin) was prepared as previously published.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Chemistry Benzo [5,6]indolo[2,1-b]quinazoline-6,14-dione (benzo[b]tryptanthrin) was prepared as previously published.…”
Section: Methodsmentioning
confidence: 99%
“…[4,5] A plethora of biological and pharmacological activities of tryptanthrin have been reported; tryptanthrin suppressed angiogenesis in a Matrigel plug assay in vivo by reducing the expression of angiogenic factors such as Ang-1, PDGFB, and MMP2, as well as VEGFR2-mediated ERK1/2 signals. [6] Tryptanthrin ameliorated clinical symptoms and skin lesions of apoptotic dermatitis induced by 2,4-dinitrofluorobenzene through down-regulation of thymic stromal lymphopoietin. [7] Tryptanthrin also showed antitumoral activity by targeting indoleamine 2,3-dioxygenase (IDO-1), and 8-fluorotryptanthrin, a stronger IDO-1 inhibitor than tryptanthrin, potently suppressed tumor growth in Lewis lung cancer tumor-bearing mice.…”
Section: Introductionmentioning
confidence: 97%
“…Neuroblastoma, an extracranial cancer that occurs most commonly in children, Inhibition of growth and colony forming ability Cellular differentiation Cell cycle arrest N-myc [103] shows amplification of N-myc in its advanced stages. Any agent that can stimulate differentiation of neuroblastoma cells and downregulate N-myc can inhibit their proliferation.…”
Section: /Adr Cellsmentioning
confidence: 99%
“…Liao et al have reported that tryptanthrin has the ability to inhibit angiogenesis, one of the key steps in tumor growth and metastasis by targeting the VEGFR2-mediated ERK1/2 signaling pathway both in in vitro and in vivo conditions [103].…”
Section: Angiogenesismentioning
confidence: 99%
“…With a general interest in dissecting VEGFR2 signaling, a growing number of evidence demonstrates that VEGFR2 is predominantly responsible for responses of vascular endothelial cells to VEGF under both physiological and pathological conditions, and plays important role in the process of angiogenesis through affecting vascular permeability, proliferation, survival and migration (9,10). However, as a therapeutic target, the attractiveness of VEGFR2 is multifaceted.…”
Section: Introductionmentioning
confidence: 99%